Shakespeare and violence prevention: a practical handbook for educators - Giguere, Amanda, author; University of Wyoming Press, publisher (Colorado State University. Libraries, 2025)
This handbook explores the potential for Shakespeare's plays to address public health issues of youth & violence. It offers entry points, research, and practical experiences to align a violence prevention curriculum modeled after work of an outreach program created at CU Boulder.--Provided by publisher.
Interlude: the tragedies and violence prevention -- Macbeth: empathy and violence -- Julius Caesar: targeted attacks and warning signs -- Romeo and Juliet: suicide and community violence -- Interlude: the comedies and violence prevention -- Much ado about nothing: "the merry war": rumors, gossip, and school climate -- Twelfth night: bullying and cyberbullying -- The comedy of errors: presence, breath, and mindfulness -- The taming of the shrew: gender and relationship violence -- The Tempest: Prospero's "rarer action": forgiveness and breaking the cycle of violence.
Keywords: Shakespeare, William, 1564-1616 -- Criticism and interpretation; Shakespeare, William, 1564-1616 -- Study and teaching (Secondary); Violence in literature; English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism; School violence -- Prevention -- Study and teaching (Secondary)